Eco-friendly hydrothermal synthesis of Co3O4-based NiO–Fe2O3 binary and ternary nanocomposites for electrochemical energy storage applications - Khalid Saifullah; Kamran Ullah; Najmul Hassan; Tayyaba Shireen; Salah Knani; Vineet Tirth; Ali Algahtani; Abid Zaman (Electrochemistry Communications)
The increasing global demand for advanced energy storage technologies necessitates the development of high-performance materials. In this study, Co3O4-based NiO-Fe2O3 binary and ternary nanocomposites were synthesized via a green hydrothermal method using banana peel extract as a sustainable reducing agent. The Phase analysis, microstructural, elemental composition, electrochemical, and magnetic properties of synthesized materials were analyzed using X-ray diffractions (XRD), scanning electron microscope (SEM), energy dispersive x-rays (EDX), cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV), and vibrating sample magnetometry (VSM) technique. XRD analysis confirmed the coexistence of binary (NiO-Co3O4) and ternary Fe2O3-NiO-Co3O4 phases in the nanocomposite. The surface morphology analysis showed the presence of spherical and round-like shape. Electrochemical analysis revealed a high specific capacity of 2692 mAh g−1 for the Fe2O3-NiO-Co3O4 nanocomposite, significantly surpassing the binary compound. The corresponding energy densities were 391.2, 363.2, 328.2 J/mA.cm−2, with Tafel slopes of 112, 129, and 118 mV/dec, respectively. The VSM results indicated retentivity values of 1.49, 2.53, and 1.03 emu/g for NiO/Co3O4, Fe2O3/Co3O4, and Fe2O3/NiO/Co3O4 nanocomposite. The energy dispersive x-rays (EDX) spectroscopy confirmed the presence of Co, O, Fe, and Ni elements. These findings highlight the potential of Co3O4-based NiO/Fe2O3 nanocomposites as promising candidates for high performance energy and data storage applications.